ANALISIS UNSUR KESALAHAN (MENS REA) TERKAIT TINDAK PIDANA PENGANIAYAAN (STUDI KASUS PUTUSAN NOMOR : 372/PID.B/2020/PN JKT.UTR) - Pengky Stephen Sigalingging; Erdianto Effendi; Adi Tiara Putri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Cases of criminal acts of persecution continue to be in the public spotlight, this happens because there are many cases of criminal acts of persecution that cause unrest in the community. Not only cases of criminal acts of persecution that were carried out spontaneously, but also those that were planned in advance and caused serious injuries. This study explains the problems regarding the application and proof related to the element of error (mens rea) in the form of intentional and unintentional in Decision Number: 372/Pid.B/2020/PN.Jkt Utr. As there is a discrepancy with the existing actus reus and causes the element of error in the form of intentional turning into negligence. This is because there is no definite basis that can be used in applying the element of error (mens rea) in cases of criminal acts of persecution. This thesis will explore the application of the element of error (mens rea) in the case of Decision Number: 372/Pid.B/2020/PN.Jkt Utr.This type of research is normative legal research that uses case studies of literature in collecting and searching data. In this study, the authors conducted research on legal theory, namely the theory of criminal law policy and the theory of legal certainty. This research is a descriptive research, which is a research method that describes the actual situation at the time of the research through data collection which is then interpreted with each other so that the formulation and analysis of an existing problem is obtained. Data analysis used by researchers in this study is qualitative data analysis, namely data analysis that does not use statistics or other things, but researchers simply describe descriptively or verbally based on the data obtained.The results of this study can be concluded in two main things. First, the evidence and application of the element of error (mens rea) by the Panel of Judges in the North Jakarta District Court Decision Number: 372/Pid.B/2020/PN.Jkt.Utr is considered inappropriate. As in the proof and application of the element of guilt (mens rea) in the case, the judge stated that the consequences of the act were not included in the mens rea so that the act was considered as negligence. Meanwhile, the act should have entered the realm of